Metode Pengusangan Cepat untuk Pengujian Vigor Daya Simpan Benih Cabai (Capsicum annuumL.) - Ekowahyuni, Luluk Prihastuti; Sutjahjo, Surjono Hadi; Sujiprihati, Sriani; Suhartanto, Mohamad Rahmad; Syukur, Muhamad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2012)
The ability of seed to maintain seed quality during storage is called seed vigor. Accurate method for seed vigor testing of pepper seeds is necessary to accurately determine seed storability during seed distribution. The aim of this research was to determine the best accelerated aging method (AAM) of pepper seed. Freshly harvested seeds of Capsicum annuumL., IPB C9 genotype were used in this study. The experiment used randomized complete block design (RCBD) with three replications. The experimental treatments were seed vigor testing methods i.e. natural deterioration test at room temperature in controlled humidity (RH 90-95%), and four AAM (hot water 60 ºC, methanol 20%, ethanol 20%, and high temperature at 40 ºC). The best method was selected using analysis of variance, coeficient of variance, regresion dan t student analysis. AAM using 20% methanol at periods of 0, 2, 4, 6 and 8 hours was the best method of seed vigor testing for pepper seed. Keywords: accelerated aging, deterioration, ethanol, methanol, high temperature